Biologic mesh infection with Candida albicans after abdominal wall reconstruction with calcium sulphate antibiotic beads: A case report. (2021) - Brennan, Kelly; Patel, Pooja; Drohan, Ashley; Minor, Samuel
Abstract: Mesh infection after abdominal wall reconstruction is a rare and usually devastating complication. Herein, we describe a unique case of a delayed and non-lethal Candida albicans mesh infection after abdominal wall reconstruction with placement of a biologic graft impregnated with antibiotics. Mesh explantation was not required, and the wound healed by secondary intention. This work suggests that locally delivered antibiotics may change the culprit microbes of skin infections to more unusual species such as Candida spp. Future research is required to study the effect of including antifungal agents in the locally delivered antimicrobials for abdominal wall reconstructions with biological meshes.